Quantity of adipose tissue and adipose tissue dysfunction and the risk of cancer in individuals at high risk of cardiovascular disease. (3rd October 2022) - Helmink, M A G; Westerink, J; De Valk, H W; De Ranitz-Greven, W L; Visseren, F L J
Abstract: Background: Individuals with cardiovascular disease (CVD) are at increased risk of cancer compared to the general population. Adipose tissue dysfunction, as a consequence of excess adipose tissue, contributes to this risk via production of several hormones and cytokines. Whether the high risk of cancer in people with type 2 diabetes (T2D) is mainly attributable to the quantity of adipose tissue or the degree of adipose tissue dysfunction, is unknown. Purpose: To assess the relation between the quantity of adipose tissue and adipose tissue dysfunction and the risk of cancer in a cohort of patients at high risk of CVD, with and without T2D. Methods: 10792 participants from the UCC-SMART study were included for this prospective cohort study, including 7026 individuals with a history of CVD and 1769 individuals with pre-existent T2D. The effect of quantitative measures of adiposity [BMI, waist circumference and ultrasonographically determined visceral adipose tissue (VAT)] and of the degree of adipose tissue dysfunction on the risk of cancer was assessed using Cox proportional hazards models adjusted for confounders. Adipose tissue dysfunction was quantified by metabolic dysfunction (modified metabolic syndrome criteria with waist circumference replaced by hsCRP), the estimated glucose disposal rate (eGDR, a measure of insulin resistance), and HOMA-IR (only in people without T2D). Potential effect modification by T2D was tested by adding an interaction term to the models. Results: During a median of 8.6 (IQR 5.0–12.8) years of follow-up, 1164 individuals were diagnosed with cancer, of which 219 individuals had pre-existent T2D. Incidence rates were 14.0 and 11.6 per 1000 person-years for people with and without T2D, respectively. Increases per SD in BMI [HR 0.98 (95% CI 0.92–1.05)], waist circumference [HR 1.01 (95% CI 0.95–1.09)] and VAT [HR 1.03 (95% CI 0.97–1.10)] were not significantly associated with an increased risk of cancer. These relations were not different for people with and without T2D (p>0.05). Metabolic dysfunction was associated with a higher risk of cancer [4–5 vs. 0–1 components: HR 1.14 (95% CI 1.03–1.25)]. The relation between eGDR and incident malignancy was different for people without T2D [HR 0.97 (95% CI 0.93–1.01)] than for people with T2D [HR 1.06 (95% CI 0.97–1.16)] (p=0.04), with this last relation being more pronounced in people with a higher amount of VAT. No significant relation was observed between HOMA-IR and the risk of cancer in people without T2D [HR 0.99 (95% CI 0.96–1.02)]. Conclusion: Adipose tissue dysfunction, assessed by the degree of metabolic dysfunction, is associated with a higher risk of cancer in people at high risk of CVD. No significant associations were observed for quantitative measures of adiposity. The higher risk of cancer among individuals with adipose tissue dysfunction warrants awareness among clinicians and emphasizes the importance of obesity prevention. Funding Acknowledgement: Type of funding sources: None.